The ERCC4/XPF gene polymorphism in postmenopausal women with breast cancer - Sobczuk, Anna; Smolarz, Beata; Romanowicz-Makowska, Hanna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Background: The ERCC4/XPF gene plays an important role in the DNA repair system. Objective: Arg415Gln polymorphism in the ERCC4/XPF gene in postmenopausal women with breast cancer was analysed. Material and methods. Blood samples were obtained from 100 women with breast cancer and controls (n=106). The polymorphisms were determined by PCR-RFLP. Results: The distribution of the genotypes of the Arg415Gln polymorphism of ERCC4/XPF in both controls and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences (p>0.05) in genotype distributions or allele frequencies between subgroups assigned to histological stage. Conclusion: The results suggest that Arg415Gln polymorphism in ERCC4/XPF may not be linked with appearance and development of breast cancer.